Increasing Incidence of Early Onset Locally Advanced Colorectal Cancer: Does Adjuvant Treatment Has a Clinical Improvement? - Budhi Ida Bagus (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2024)
The global prevalence of early-onset colorectal cancer (EO-CRC) has exhibited a notable upward trend, thereby emerging as a significant concern within the realm of public health. The clinical, genetic, molecular, and histological characteristics of this condition indicate that it may be a separate entity, exhibiting a higher level of aggression. Nevertheless, it appears that both genetic and environmental risk factors play a role in the observed epidemiological change in the incidence of colorectal cancer (CRC). Further evidence is required to elucidate the etiology of EO-CRC and to formulate effective screening and management approaches. The management of colorectal cancer in young adults is an unmet clinical need, given that the disease may result in the greatest loss of years of life in this demographic upon diagnosis. The incidence of colorectal cancer (CRC) in people under 50 has been rising annually since early 1990 at a rate of 2%. Since the frequency of CRC has been declining overall, the rise in the disease's incidence among young adults is especially concerning. The primary tumor of early-onset colorectal cancer (CRC) is located on the left side of the colon and is associated with poorer cell differentiation, a higher prevalence of signet ring cell histology, and an advanced stage at diagnosis. 20% of patients have familial colorectal cancer (CRC), and about 30% of patients have tumors containing mutations that cause hereditary cancer predisposing syndromes. 20% of patients have familial colorectal cancer (CRC), and about 30% of patients have tumors containing mutations that cause hereditary cancer predisposing syndromes.